The Effect of Problem Based Learning Model on Front Kick Mastery in Pencak Silat Learning at SMA Negeri 2 Karawang - Kiki Hidayattullah; Rahmat Iqbal; Astri Ayu Irawan (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study, among others, is to determine the effect of the problem based learning on the mastery of the front kick movement in learning pencak silat at SMA Negeri 2 Karawang. This study uses an experimental quantitative approach. This study was made using a pre-experimental form of a one group pretest-posttest design. The place of this research is in SMA Negeri 2 Karawang. This research was conducted in July – August 2022 with 8 meetings. The population in this study was class XI students at SMA Negeri 2 Karawang. Sampling using the technique of